ANALISIS PERKEMBANGAN INTERAKSI SOSIAL ANAK BERKEBUTUHAN KHUSUS DI UPT SDN 263 GRESIK - Dwi Putri Aisyah; Arya Setya Nugroho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Children with special needs have various problems ranging from social interaction, how to communicate and others. However, if we examine more deeply about the problem, it is not all children with special needs cannot communicate well with friends or other people. This study aims to determine the development of social interaction of children with special needs at UPT SDN 263 Gresik. Not only that, this study aims to find out what types of children with special needs there are as well as to find out the coaching or teaching and learning process at UPT SDN 263 Gresik. By using a qualitative descriptive method. The subjects in this study were one of the special assistant teachers (GPK), several children with special needs and normal children at UPT SDN 263 Gresik. By using data collection techniques and using interviews as well as observation and documentation. Using observation sheet instruments and cameras for documentation. This study describes the condition of classrooms that are mixed between normal or regular children and children with special needs, by observing the development of social interactions between them. Using local language and local signs for regular children, and using sign language and having imitative behavior and sensitive behavior is difficult to control emotions with regular students. Teacher coaching strategies are also considered in this study.